Representation of Gender Ideology Issue in Matt Walsh’s Speech - Shavina Lestiani; Suprayogi Suprayogi; Rizma Amalia Sa’adah (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
As the researches on gender ideology seen from critical discourse analysis perspective has been limitedly conducted, this research is aimed at filling this gap. This research reveals the representation of gender ideology issue in Matt Walsh’ Speech. Employing qualitative methods using Van Dijk’s Critical Discourse Analysis framework, this research focused on the speech from Walsh’s Youtube Channel delivered in Centennial Institute's 2022 Western Conservative Summit on gender ideology issues. The the micro aspects of language or microstructure, namely the lexical, syntactic, semantics and rhetorical aspects becomes the focus of the research. The finding suggest that gender ideology is represented negatively through exclusive pronoun, adjective, noun, verb, anaphora, metaphor, paradox, and many others stating that gender ideology is a weak concept but influencing massively.